Morphological and phylogenetic analyses of Bipolaris species associated with Poales and Asparagales host plants in Iran - Ahmadpour, Abdollah; Heidarian, Zeinab; Ghosta, Youbert; Alavi, Zahra; Alavi, Fatemeh; Manamgoda, Dimuthu S.; Kumla, Jaturong; Karunarathna, Samantha C.; Rampelotto, Pabulo Henrique; Suwannarach, Nakarin (Frontiers in Cellular and Infection Microbiology, 2025)
Bipolaris species exhibit various ecological roles, including plant pathogens, epiphytes, saprophytes, or endophytes, primarily associated with poaceous hosts, including cultivated cereals. Iran is known for its diverse climates and rich flora, which serve as a hotspot for fungal diversity. In this study, to determine the species diversity of Bipolaris associated with members of the Poales and Asparagales plant orders, samples with leaf and stem lesion symptoms were collected from these plants across various locations in Iran between 2010 and 2022. Based on the morphological characteristics and multi-locus phylogeny (ITS−rDNA, GAPDH, and TEF1), nine Bipolaris species were identified: Bipolaris avrinica sp. nov., Bipolaris azarbaijanica sp. nov., Bipolaris banihashemii sp. nov., Bipolaris hedjaroudei sp. nov., Bipolaris hemerocallidis sp. nov., Bipolaris iranica sp. nov., Bipolaris persica sp. nov., Bipolaris crotonis, and Bipolaris salkadehensis. B. crotonis represents a new record for Iran’s funga, while B. salkadehensis has been documented on several new hosts globally. The study provides detailed morphological descriptions and illustrations of all identified species, along with insights into their habitats, distributions, and phylogenetic relationships within the Bipolaris genus. This study also emphasizes the need for further research into fungal biodiversity in Iran and provides significant data on the distribution and host range of Bipolaris species.